If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 24 = y + -12 Reorder the terms: 24 + 3y = y + -12 Reorder the terms: 24 + 3y = -12 + y Solving 24 + 3y = -12 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 24 + 3y + -1y = -12 + y + -1y Combine like terms: 3y + -1y = 2y 24 + 2y = -12 + y + -1y Combine like terms: y + -1y = 0 24 + 2y = -12 + 0 24 + 2y = -12 Add '-24' to each side of the equation. 24 + -24 + 2y = -12 + -24 Combine like terms: 24 + -24 = 0 0 + 2y = -12 + -24 2y = -12 + -24 Combine like terms: -12 + -24 = -36 2y = -36 Divide each side by '2'. y = -18 Simplifying y = -18
| 4(x*2)=32 | | 49x^2+0x-144=0 | | 212+1=-3(2q-1)+4(2q+1) | | x^3+11x-13=0 | | 8n-3=-15+6n | | 9-6n+2n=23-98 | | 3s-4=2+6s | | -3.2=1+(-0.2) | | x=243 | | 7y-3=3 | | 12(5c-1)-4=58c+12 | | 14x-6x=56 | | 24+10x-x^2=0 | | 14x-6x=54 | | 12x-6x=54 | | 9z-5z=6 | | 5x+1-3x-64x+16=16x-1 | | -3y-8=6y+10 | | (4x^2)=36 | | 4(7x-2)=29x | | -5c+3=-2 | | (5x+20)=360 | | 4(4c-1)-5=13c+3 | | 5x+(20)=360 | | -39+6y+3=3(4y-2)-6 | | 33+4y-14=14y-9-3y | | -30y+95-35+2y=-24 | | -x+5x+6=8x+36 | | 6p^2+2p+3=0 | | 6p^2+2p-3=0 | | 4(x+2)=14-2(3-2x) | | 19.55=44.3-2.5x |